SAT0089 FEATURES OF THE SECRETION OF INTERLEUKIN-6, INTERLEUKIN-10, TUMOR NECROSIS FACTOR ALPHA IN PATIENTS WITH RHEUMATOID ARTHRITIS ASSOCIATED WITH ANEMIA. (2nd June 2020) - Sakhin, V.; Grigoriev, M.; Rukavitsyn, O.; Kryukov, E.; Kazakov, S.
Abstract : Background: Anemia is widespread in rheumatic patients and is an important extra-articular manifestation that correlates with physical disability and increased mortality. The pathogenesis of such anemia is complex and multifactorial, including due to the influence of pro-inflammatory cytokines. Objectives: Our aim was to study the characteristics of the secretion of interleukin-6 (IL-6), interleukin-10 (IL-10), tumor necrosis factor-alpha (TNF-α) in patients with rheumatoid arthritis (RA) with anemia of chronic diseases (ACD), iron deficiency anemia (IDA) and a combination of ACD / IDA, as well as to study the effect of these cytokines on the development of anemia. Methods: There were examined 69 (54 (7 men /47 women, 50.6 ± 4.1 years) with anemia, 15 (6 men/9 women, 53.5 ± 2.74 years) without anemia) of RA patients. According to the criteria of Van Santen and Worwood, by determining the transferrin saturation index (TSI), ferritin, C-reactive protein (CRP), patients were divided into 4 groups: group 1 - ACD, 22 (5/17) patients (hemoglobin 79 [IQR, 95.6-111], red blood cells 3.5 [IQR, 3.6-4], TSI 25 [IQR, 14.7-26.2], ferritin 326.2 [IQR, 197.8-451.7], CRP 63.7 [IQR, 10.2-104.8]), group 2 - ACD / IDA, 18 (0/18) patients (hemoglobin 101 [IQR, 94-114], red blood cells 3.9 [IQR, 4-4.4], TSI 12.5 [IQR, 7.7-15], ferritin 50.1 [IQR, 11.9-74.9], CRP 45.8 [IQR, 17.6-54.9]), group 3 - IDA, 14 (2/12) patients (hemoglobin 108 [IQR, 100-115], red blood cells 4.5 [IQR, 4.1-4.9], TSI 9.7 [IQR 3-14], ferritin 21.8 [IQR, 7.2-28.9], CRP 8.6 [IQR, 2.7-8.6]), group 4 (control) - 15 patients without anemia (hemoglobin 141.4 [IQR, 133-147], red blood cells 4.6 [IQR, 4.3-4.9], TSI 23.1 [IQR, 16.6-27.8], ferritin 78.5 [IQR, 36-90.7], CRP 4.6 [IQR, 1.2-5.8]). The diagnosis of rheumatoid arthritis was made based on the 2010 ACR/EULAR classification criteria. The number of red blood cells and hemoglobin levels were determined on a Sysmex XS-500i analyzer (Japan). Concentrations of ferritin, CRP, TSI were determined on an Olympus Au 480 analyzer (Beckman Coulter, USA). Concentrations of IL-6, IL-10, and TNF-α were determined using a Stat Fax 2100 analyzer (Awareness Technology Inc., USA). The significance of differences between several unrelated groups was determined using the Kruskal-Wallis test at a significance level (p) of less than 0.05. To assess the relationship between the variables, the Spearman correlation coefficient (r) was calculated Results: In the ACD group, there were the highest concentrations of CRP, ferritin in comparison with the other groups (p <0.05). TSI in the ACD group was higher compared with the IDA and ACD / IDA groups (p <0.05) and did not differ from the control group (p> 0.05). The maximum concentration of IL-6 was found in the ACD group (36.2 [IQR, 6.7-41]) compared with the ACD / IDA group (21.7 [IQR, 7.2-20.4]) (p <0, 05) and the IDA group (5.9 [IQR, 1.5-3.7]) (p <0.05) and without anemia (2.7 [IQR, 1.5-3) (p <0.05). Regarding IL-10 and TNF-α, no intergroup differences were found. A moderate correlation was found between the number of red blood cells and the concentration of IL-6 (r = -0.3), IL-10 (r = -0.4), TNF-α (r = -0.3). The relationship between the concentration of hemoglobin and IL-6 (r = -0.6), IL-10 (r = -0.4), TNF-α (r = -0.3) was revealed. Conclusion: In RA patients, IDA, ACD, as well as their combination, may occur. It is very important to clarify the genesis of anemia. ACD should be isolated separately because it has a complex pathogenesis, one of the important components of which are cytokines and their effect on erythropoiesis. The increased concentration of IL-6 in the group of patients with ACD, as well as the presence of a correlation between IL-6, red blood cells and hemoglobin, indicate the importance of this cytokine in the development of anemia. An increase in the concentration of ferritin and CRP also reflects the inflammatory genesis of anemia in patients with this anemia. The presence of a correlation between IL-10, TNF-α and hemogram indices suggests their influence on the development of anemia. Disclosure of Interests: None declared